A Numerical Study for Robust Active Portfolio Management with Worst-Case Downside Risk Measure. (31st March 2014) - Ling, Aifan; Tang, Le
Abstract : Recently, active portfolio management problems are paid close attention by many researchers due to the explosion of fund industries. We consider a numerical study of a robust active portfolio selection model with downside risk and multiple weights constraints in this paper. We compare the numerical performance of solutions with the classical mean-variance tracking error model and the naive 1 / N portfolio strategy by real market data from China market and other markets. We find from the numerical results that the tested active models are more attractive and robust than the compared models.